Liquid Organic Fertilizers for Sustainable Agriculture: Nutrient Uptake of Organic versus Mineral Fertilizers in Citrus Trees - Martínez-Alcántara, Belén; Martínez-Cuenca, Mary-Rus; Bermejo, Almudena; Legaz, Francisco; Quinones, Ana (PLOS, 2020)
The main objective of this study was to compare the performance of two liquid organic fertilizers, an animal and a plant-based fertilizer, with mineral fertilization on citrus trees. The source of the fertilizer (mineral or organic) had significant effect in the nutritional status of the organic and conventionally managed mandarins. Nutrient uptake, vegetative growth, carbohydrate synthesis and soil characteristics were analyzed. Results showed that plants fertilized with animal based liquid fertilizers exhibited higher total biomass with a more profuse development of new developing organs (leaves and fibrous roots). Liquid organic fertilization resulted in an increased uptake of macro and micronutrients compared to mineral fertilized trees. Moreover, organic fertilization positively affected the carbohydrate content (fructose, glucose and sucrose) mainly in summer flush leaves. Liquid organic fertilization also resulted in an increase of soil organic matter content. Animal-based fertilizer, due to intrinsic composition, increased total tree biomass and carbohydrate leaves content, and led to lower soil nitrate concentration and higher P and Mg exchangeable in soil extract compared to vegetal-based fertilizer. Therefore, liquid organic fertilizers could be used as an alternative to traditional mineral fertilization in drip irrigated citrus trees.